An Experimental Study on the Reinforcement of Silt with Permeable Polyurethane by Penetration Grouting. (28th November 2020) - Wang, Chaojie; Liu, Qi; Guo, Chengchao; Xia, Yangyang; Hao, Yanjie; Shi, Mingsheng; Zhao, Peng
Abstract : To meet the demand of antiseepage and reinforcement of soil dams, a kind of permeable polyurethane grouting material was developed. A visual steady-pressure grouting test device was designed to study the law of polyurethane diffusion and reinforcement in silt under different pressure, and the interaction mechanism of grout and soil body structure was explored microscopically. The results showed that, with the increase in the grouting pressure, the diffusion speed rose, and the diffusion pattern of grout in the soil also changed from permeation diffusion to permeation splitting. Under the effect of grouting pressure, more tiny cracks will occur in the soil structure, leading to the use of more grout, thus increasing the strength of the consolidated soil by more than 10 times. The results of SEM-EDS and mercury intrusion test proved that the polyurethane had a significant filling effect on the soil structure, which could effectively reduce the porosity of the soil and cement the soil particles through wrapping, complexing, and hydrogen bonding, thereby improving the soil properties. Moreover, the results revealed from a microscopic perspective that the grouting altered the pore structure of the soil structure through the seepage-erosion-splitting coupling effect, but when the grouting pressure exceeded 0.4 MPa, the soil particle and grout would be partially remixed and arranged closely, showing a phenomenon of jet grouting. Finally, the material was used in engineering practice, achieving a satisfactory grouting treatment effect.